(untitled) (Journal of Human Sciences, 2025)
The research paper "The Impact of Human Resource Management Practices on the Quality of Health Services in the Libyan Health Sector with Application to Waddan General Hospital" analyzes the impact of human resource management practices on the quality of health services. The study aims to determine the impact of human resource training and compensation, in addition to the impact of employee selection and appointment on the quality of health care. Data was collected from 71 employees using a questionnaire, and the results showed a limited impact of human resource selection and appointment on the quality of services. While human resource compensation showed a positive impact, the relationship between human resource training and service quality was statistically significant but weak. Employees were satisfied with the training programs meeting their needs, but they felt that the salary system was unfair, and rewards were ineffective in improving performance. The study recommends simplifying appointment procedures and improving selection criteria, in addition to reviewing the salary structure to ensure fairness and competitiveness. It also calls for enhancing the training environment and customizing programs according to employee needs, while clarifying incentive criteria. These results contribute to understanding how to improve the quality of health services by improving human resource management practices at Waddan General Hospital, reflecting the importance of investing in the human element to achieve better results in the Libyan health sector